Provision of day-case local anesthetic thoracoscopy: A multicenter review of practice. - Psallidas, I; Corcoran, J; Fallon, J; Bintcliffe, O; Sivasothy, P; Maskell, N; Maldonado, F; Pepperell, J; Rahman, N (Elsevier, 2017)
Pleural disease is a common health problem and it is estimated to affect over 3,000 people per million population. Pleural effusion is the most common condition among the group and in approximately 75% of cases the clinical history, physical examination, radiographic techniques and pleural fluid analysis will identify a cause for the pleural effusion, with the remaining 25% requiring further invasive diagnostic procedures. An increasing trend has been seen in the number of centres performing local anaesthetic thoracoscopy (LAT) as a gold-standard diagnostic and/or therapeutic procedure. There is previous evidence from a single site that the technique can be performed on a day-case basis without compromising its efficacy and safety. This is the first multicentre study assessing LAT as a day case procedure and includes data from 4 centres in the UK and 1 centre in the USA. The primary aim of this paper was to report data on safety, feasibility and outcomes of day-case LAT.